Meta-Analisis: Efektivitas Implementasi Media Pembelajaran Menggunakan TIK Pada Mata Pelajaran Kewirausahaan - Ananda, Yulia Fitri; Ganefri, Ganefri; Yulastri, Asmar (PAKAR Pendidikan, 2024)
The learning process is a fundamental aspect that supports the development of knowledge, skills and attitudes among learners. Along with the advancement of digital technology, there has been a substantial integration of ICT-based learning tools that aim to improve student engagement and educational outcomes. Despite the availability of innovative tools, many educators still use conventional methodologies, often resulting in passive and less effective learning environments. Recent empirical studies emphasize the importance of ICT-based educational tools in entrepreneurship education. Tools such as educational videos, electronic modules and interactive platforms facilitate direct interaction between educators and learners. In addition, simulations and multimedia resources can be utilized to explain complex concepts, enhancing student understanding. The study used a meta-analysis approach to assess the efficacy of ICT-based educational media in improving learning outcomes in entrepreneurship education. By analyzing secondary data from pre-test and post-test results featured in ten scholarly articles retrieved from Google Scholar, the study calculated effect sizes and conducted hypothesis testing through paired sample t-tests. The analysis revealed a two-tailed significant p-value of 0.000, lower than the threshold value 0.05, leading to the acceptance of the alternative hypothesis. Consequently, there was a marked increase in the mean score from 61.793 to 84.131, indicating an increase of 19.5%. The findings suggest that ICT-based educational tools enhance student learning and are specifically effective in entrepreneurship education, with a Cohen effect size of 1.58.